2012
DOI: 10.5923/j.ijpbs.20120206.08
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Correlates of HIV-related Sexual Risk Factors among Male Clients in Southern India

Abstract: Psychosocial theories suggest that individuals' behavior is a reflect ion of their intention and ability to carry out a typical behavior. Th is study proposes to examine the psychosocial correlates of HIV-related sexual risk factor among male clients of female sex workers (FSWs). Data were used from a cross-sectional survey, collected using two-stage sampling, conducted among 2382 clients of FSWs in four states of India in November 2008. Clients were males who had engaged in paid sex with a FSW in the 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…Consistent with previous studies [10, 13, 41] our results strongly support the hypothesis that condom self-efficacy is associated with a higher likelihood of consistent condom use. Despite controlling for relevant covariates, the magnitude and direction of effect of condom self-efficacy on consistent condom use persist.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies [10, 13, 41] our results strongly support the hypothesis that condom self-efficacy is associated with a higher likelihood of consistent condom use. Despite controlling for relevant covariates, the magnitude and direction of effect of condom self-efficacy on consistent condom use persist.…”
Section: Discussionsupporting
confidence: 92%
“…Trust, unavailability of condoms, dislike of condoms and perceptions that condoms reduce sexual pleasure were the main reasons for inconsistent use of condoms among students – all of which corroborated previous studies [1113, 29, 30]. Also, a previous study conducted among Nigerian university students has shown that despite being aware of the risks associated with unprotected sex, Nigerian students engage in risky sexual behaviour due to perceptions that condoms reduce sexual pleasure and the often unfounded belief that their partners are free of any sexually transmitted diseases [3].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Literature reported that self-efficacy is one of the most significant predictors of condom use. [14][15][16][17][18] According to social cognitive theory, self-efficacy is a central concept in which both outcome and efficacy of expectations are critical in the promotion of health and behavioral change. 19 Bandura 20 defines the term "self-efficacy" as a "judgment of one's capability to accomplish a certain level of performance".…”
Section: Introductionmentioning
confidence: 99%